Diagnosis, surgical treatment, and management of borderline ovarian surface epithelial neoplasms: Report of 2 cases and review of literature - Michael Canfarotta; Eileen Gillan; Fabiola Balarezo; Brendan Campbell; Anthony Tsai; Christine Finck (Elsevier, 2014)
Ovarian borderline surface epithelial neoplasms occur infrequently in the pediatric population. Preoperative diagnostic criteria include ultrasound and serum tumor markers with definitive diagnosis made on pathologic examinations intraoperatively. Treatment typically involves resection of the tumor with an emphasis on preserving fertility. Patients diagnosed with borderline tumors generally have a good prognosis; however the possibility of recurrence remains. Two cases of 15 year-old females with borderline ovarian tumors are presented that add to the current literature by highlighting the diagnosis, clinical management, and follow-up postoperatively.